2022
DOI: 10.1007/s10877-022-00907-0
|View full text |Cite
|
Sign up to set email alerts
|

Humidity and measurement of volatile propofol using MCC-IMS (EDMON)

Abstract: The bedside Exhaled Drug MONitor – EDMON measures exhaled propofol in ppbv every minute based on multi-capillary column – ion mobility spectrometry (MCC-IMS). The MCC pre-separates gas samples, thereby reducing the influence of the high humidity in human breath. However, preliminary analyses identified substantial measurement deviations between dry and humid calibration standards. We therefore performed an analytical validation of the EDMON to evaluate the influence of humidity on measurement performance. A ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This VUV TOF-MS achieved a limit of quantification at 0.12 ppbv, satisfying the requirements for measuring exhaled propofol concentration in humans. Compared with the device of Edmon, our apparatus experiences less interference from water resulting in more stable output results [9]. Our pilot study demonstrated its capability to simultaneously determine the concentrations of various anesthetics, including propofol, ciprofol [18,19], fos-propofol, sevoflurane, and desflurane.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This VUV TOF-MS achieved a limit of quantification at 0.12 ppbv, satisfying the requirements for measuring exhaled propofol concentration in humans. Compared with the device of Edmon, our apparatus experiences less interference from water resulting in more stable output results [9]. Our pilot study demonstrated its capability to simultaneously determine the concentrations of various anesthetics, including propofol, ciprofol [18,19], fos-propofol, sevoflurane, and desflurane.…”
Section: Discussionmentioning
confidence: 95%
“…However, these instruments still have disadvantages such as loud noise and large volume [6]. Although devices based on ion mobility spectrometry (IMS) are small in size [7,8], such as Edmon, a product based on multi-capillary column-IMS (MCC-IMS) launched in 2017, its sensitivity can be easily affected by moisture [9].…”
Section: Introductionmentioning
confidence: 99%
“…17 The performance of IMS is easily disturbed by humidity, which is high in exhaled breath. 18 Using UV-TOFMS, gas samples can be analysed online without pre-separation. The sensitivity of UV-TOFMS can reach the pptv level and it is insensitive to humidity, which meets the requirements for the detection of trace volatile organic compounds in exhaled breath.…”
Section: Discussionmentioning
confidence: 99%